2021
DOI: 10.1371/journal.pone.0260425
|View full text |Cite
|
Sign up to set email alerts
|

Shifting gender norms to improve HIV service uptake: Qualitative findings from a large-scale community mobilization intervention in rural South Africa

Abstract: Background Interventions to improve HIV service uptake are increasingly addressing inequitable and restrictive gender norms. Yet comparatively little is known about which gender norms are most salient for HIV testing and treatment and how changing these specific norms translates into HIV service uptake. To explore these questions, we implemented a qualitative study during a community mobilization trial targeting social barriers to HIV service uptake in South Africa. Methods We conducted 55 in-depth interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Qualitative data from our trial found evidence that Tsima brought about improved treatment literacy and that understanding the benefits of early and consistent HIV treatment motivated participants to engage in testing and care by reducing stigmarelated fears associated with a positive diagnosis. 31 Because stigma is unlikely to resolve by increasing service delivery alone, 32 less focus on stigma could have played a part in diminishing the impact of some of the test and treat trials, 30 driving home the need for continued innovation in the field of stigma reduction. These innovations are most urgently needed for men, where entry to care through HIV testing continues to pose the greatest barrier to achieving national targets.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative data from our trial found evidence that Tsima brought about improved treatment literacy and that understanding the benefits of early and consistent HIV treatment motivated participants to engage in testing and care by reducing stigmarelated fears associated with a positive diagnosis. 31 Because stigma is unlikely to resolve by increasing service delivery alone, 32 less focus on stigma could have played a part in diminishing the impact of some of the test and treat trials, 30 driving home the need for continued innovation in the field of stigma reduction. These innovations are most urgently needed for men, where entry to care through HIV testing continues to pose the greatest barrier to achieving national targets.…”
Section: Discussionmentioning
confidence: 99%